ANALISIS FITOKIMIA EKSTRAK KAYU EBONI (Diospyros celebica Bakh.) - Ariyanti, Ariyanti; Budiarso, Edi; Budi, Agus Sulistyo; Kusuma, Irawan W. (Jurnal Warta Rimba, 2016)
The purpose of this study was to determine the resistant-termite activity through phytochemical analysis with color test methods and compounds from the extracts of ebony. The results of this study are expected to provide early information about the biological activity of extracts of ebony as a natural anti-termite and the possibility of its utilization as a natural preservative in wood preservation. Ebony (Diospyros celebica Bakh.) have a 1th durable class and 1th strong class. Ebony is the endemic species in Central Sulawesi. The methods of maceration ebony powder, extract ethanol, extraction and fractionation and phytochemical analysis through tests of alkoloid, flavonoid, terpenoid, tannin,Â  saponin, steroid, carotenoid andÂ  cumarin were applied in this research. The results showed that the extract of ebony contains alkaloids in acetone, n-hexane, ethyl acetate, acetone and methanol. Flavonoid compound was found only in the solvent n - hexane. Tannin compound only on the solvent of ethyl acetate. Saponin compound contained in the acetone and methanol solvents. Steroid compound contained in the acetone and methanol solvents. Carotenoid compound is unfound in all solvents. Carbohydrate compound found only in ethanol. Terpenoids compound found in the acetone and methanol solvents. Cumarin compound contained only in n - hexane.Key words : anti termite, extractive, eboni wood, phytochemical analysis.